Influence of centre expertise on the diagnosis and management of hypertrophic cardiomyopathy: A study from the French register of hypertrophic cardiomyopathy (REMY). (15th January 2019) - Mirabel, Mariana; Damy, Thibaud; Donal, Erwan; Huttin, Olivier; Labombarda, Fabien; Eicher, Jean-Christophe; Cervino, Claudio; Laurito, Marianna; Offredo, Lucile; Tafflet, Muriel; Jouven, Xavier; Giura, Geltrude; et al.
Abstract: Background: Our knowledge of hypertrophic cardiomyopathy (HCM) mainly originates from quarternary centres. The objective is to assess the current management of HCM patients in a large multicentre French register according to the level of expertise. Methods and results: A total of 1431 HCM patients were recruited across 26 (11 expert and 15 non-expert) centres in REMY, a prospective hospital-based register of adult HCM patients. A sarcomeric origin was suspected in 1284 (89.7%) patients [261 (20.3%) with a reported gene mutation, 242 (18.8%) genotype-negative], while 107 (7.5%) had a diagnosis of non-sarcomeric HCM. Patients managed in non-expert centres were older (P < 0.01) and presented more often with NYHA III/IV class dyspnoea (P < 0.01), congestive heart failure (P < 0.01), low LEVF (P < 0.01), less often with a syncope history (P < 0.01) and lower LV obstruction (P < 0.01) than patients in expert centres. Genotype positive sarcomeric aetiologies were less frequent in non-expert centres (P < 0.01). The use of diagnostic and prognostic tests as cardiac MRI (P < 0.001), genetic (P < 0.001) and alpha-galactosidase A enzyme level testing (P < 0.001), Holter ECG (P < 0.001), and exercise test (P < 0.001), was lower in non-expert centres. Septal ablation procedures using alcohol (P < 0.001) or myectomy (P < 0.001) were more frequent in expert centres. Conclusion: In real life practice, only a minority of HCM patients are identified as sarcomere positive as per genetic testing. The management of HCM patients varies according to the centre's level of expertise, with less access to diagnostic and prognostic tests in non-expert centres. Non-sarcomeric HCM may therefore be overlooked despite specific treatment in some aetiologies.